Hematocrit in the first 2 hours of life and short-term outcomes in very preterm infants: A secondary analysis from a prospective cohort study - Lanxiang Pu; Yuhong Li; Yongchao Tan; Ming Zhao; Meng Xue; Ning Jiang; Lei Huang; Zhaowen Chen (PLoS ONE, 2025)
Background Preterm birth, particularly very preterm birth (before 32 weeks of gestation), is a leading cause of neonatal morbidity and mortality. The early neonatal period is critical for preterm infants, with hematocrit levels serving as a important physiological indicator. We aimed to assess the relationship hematocrit in the first 2 hours of life and Short Outcomes in very preterm infants. Methods The research was a prospective cohort study completed by Dongli Song et al. We acquired data from the DATA DRYAD website and utilized exclusively for secondary analysis. From January 2008 to April 2014, data were gathered prospectively from eligible infants at the Santa Clara Valley Medical Center. The main outcomes included any Intraventricular Hemorrhage (IVH), any Retinopathy of Prematurity (ROP), Necrotizing Enterocolitis (NEC), chronic lung disease (CLD), and late-onset sepsis (LOS). Secondary outcomes were any intubation and any transfusion. We used multivariable logistic regression analyses to calculate adjusted odd ratio (OR) with 95% CI. Results This study included 312 patients in total. Hematocrit in the first 2 hours of life, considered as a continuous variable, was significantly associated with short-term outcomes in univariate analyses (P < 0.05). After adjusting for GA, BW, and sex, only any ROP, any intubation, and any transfusion were statistically significant. With adjustments for multiple factors, the odds ratios for any ROP and any transfusion in infants whose Hematocrit was 45 or more in the first two hours of life, compared to those with an HCT less than 45 were 0.43 (95% CI, 0.19 ~ 0.97, p = 0.043) and 0.29 (95% CI, 0.12 ~ 0.7, p = 0.006). Conclusions Our study shows that higher HCT in the first 2 hours of life was statistically significant association with decreased ROP and blood transfusion in very preterm infants. Further clinical trials are necessary to confirm and validate this association.